Exploration of attitudes and behaviors of consumers with food allergies about dining out: a focus group study - Lee, Yee Ming; Kwon, Junehee (My University, 2011)
Food allergy is a public health issue as 12 million adults are having food allergies in the U.S. The objective of the study was to investigate attitudes and behaviors of consumers with food allergies about dining out using focus groups. All sessions were audio-taped, transcribed verbatim, and analyzed using NVivo Version 8.0. Seventeen participants participated in one of four focus groups in February 2010. Participants perceived cross- contact, hidden ingredients, and long communication chain in the restaurants as potential causes of food allergic reactions. Perceived barriers to provide allergen-free food were lack of training and awareness among employees. Participants perceived buffet and ethnic cuisine restaurants as risky dining places due to cross- contact and hidden ingredients. The participants preferred eating at national brand, chain restaurants since employees were well-trained about food allergies. Participants expected the servers to strictly follow the instructions given and they also felt the needs of regulations to protect people with food allergies. Participants wished to have the major allergens and listings of ingredients on the menus. Participants suggested people with food allergies to ask for clarifications from the servers while dining out, look up food allergy information online, bring Epi-pen with them, or pack their own snacks in case allergen-free food might not be provided. Results showed that consumers with food allergies experience many difficulties in restaurants due to restaurant employees' lack of knowledge and training regarding food allergy.
Keywords: Food allergies; Attitudes; Behaviors; Restaurants; Consumers